The Impact of Chunking Granularity on Hybrid GraphRAG Architecture Performance in Mitigating Hallucinations - YUSUP MIFTAHUDDIN; AFIN MAULANA; DIASH FIRDAUS (MIND (Multimedia Artificial Intelligent Networking Database) Journal, 2026)
AbstrakPesatnya pertumbuhan literatur herbal memicu information overload yang menghambat ekstraksi data manual. Meskipun Large Language Models (LLMs) membantu otomasi, risiko halusinasi faktual pada domain medis tetap tinggi, sementara Retrieval-Augmented Generation (RAG) konvensional sering gagal menangkap hubungan relasional antar-entitas. Penelitian ini menerapkan Hybrid GraphRAG, menggabungkan pencarian vektor dan Knowledge Graph, untuk mengatasi kelemahan tersebut. Fokus utamanya adalah menguji dampak granularitas chunking (karakter, kata, kalimat) terhadap representasi pengetahuan, mengingat fragmentasi teks berisiko memutus konteks semantik. Hasil eksperimen menunjukkan bahwa chunking berbasis kalimat memberikan performa terbaik, menggandakan skor Correctness dan Recall dari 0,28 ke 0,56. Temuan ini menegaskan pentingnya menjaga keutuhan kalimat demi akurasi dan keterhubungan data dalam sistem informasi medis.  Kata kunci: Hybrid GraphRAG, Knowledge Graph, Chunking, Tanaman HerbalAbstractThe rapid growth of herbal medicine literature triggers an information overload that hinders manual data extraction. Although Large Language Models (LLMs) assist in automation, the risk of factual hallucination within the medical domain remains high, while conventional Retrieval-Augmented Generation (RAG) frequently fails to capture relational connections between entities. To address these limitations, this study implements a Hybrid GraphRAG architecture that integrates vector search and Knowledge Graphs. The primary focus is to evaluate the impact of chunking granularity (character, word, and sentence-level) on knowledge representation, considering that text fragmentation risks disrupting semantic context. Experimental results demonstrate that sentence-based chunking yields the best performance, doubling the Correctness and Recall scores from 0.28 to 0.56. These findings emphasize the importance of preserving sentence integrity for data accuracy and interconnectivity within medical information systems.Keywords:Hybrid GraphRAG, Knowledge Graph, Chunking, Herbal Plants